Conditional CAPM: Time-varying Betas in the Brazilian Market - Frances Fischberg Blank; Carlos Patricio Samanez; Tara Keshar Nanda Baidya; Fernando Antonio Lucena Aiube (Revista Brasileira de Finanças, 2014)
The conditional CAPM is characterized by time-varying market beta. Based on state-space models approach, beta behavior can be modeled as a stochastic process dependent on conditioning variables related to business cycle and estimated using Kalman filter. This paper studies alternative models for portfolios sorted by size and book-to-market ratio in the Brazilian stock market and compares their adjustment to data. Asset pricing tests based on time-series and cross-sectional approaches are also implemented. A random walk process combined with conditioning variables is the preferred model, reducing pricing errors compared to unconditional CAPM, but the errors are still significant. Cross-sectional test show that book-to-market ratio becomes less relevant, but past returns still capture cross-section variation